Local indicators of spatial association (LISA) of Indonesian workers - Caroline Caroline; FX Sugiyanto; Akhmad Syakir Kurnia; Soni Agus Irwandi (Journal of Economics, Business, and Accountancy Ventura, 2019)
The migration of Indonesian workers abroad and that of foreign workers into Indonesia made problems for the economic growth of Indonesia and ASEAN. This study attempts to analyze the patterns of spatial interaction of labor that occur in Indonesia. It used the Euclidean distance, spatial weight matrix approach to calculate the Local Indicators of Spatial Association (LISA). This study took a sample of workers in ASEAN member countries with a focus on analysis on Indonesian workers during 2004-2018. Analysis was performed using spatial panel data. The results showed that there was a change in the pattern of spatial interaction of Indonesian workers, which in 2004 had a lot of spatial interactions with workers from countries with a large workforce. However, in 2018, they interacted spatially with workers from countries with few workers. Besides, the majority of Indonesian migrants work as low-ranking workers in ASEAN countries, while the majority of foreign workers from ASEAN countries work in managerial and professional levels. This implies that the Indonesian government needs to provide technical and managerial skills, soft skills, and English for migrant workers before working abroad so that they are better able to compete with foreign workers and subsequently receive better salaries.